1995
DOI: 10.1016/0014-5793(95)00880-i
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐ribosylation of Rho enhances actin polymerization‐coupled shape oscillations in human neutrophils

Abstract: Stimulated neutrophils exhibit coordinated sinusoidal oscillations in filamentous actin content and cellular shape. We investigated the effect of inhibition of the small G protein Rho on neutrophil actin polymerization, shape changes and oscillations using a genetically engineered toxin that enters cells and selectively ADP-ribosylates endogenous Rho. This treatment increased the amplitudes and frequencies of shape oscillations and duration of the oscillating transient. However, it had no effect on the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We observed previously that Rho-kinase inhibition does not affect actin reorganization in human neutrophils (Niggli, 1999). Moreover, Rho inhibition in neutrophils did not suppress chemotactic-peptide-induced actin polymerization (Ehrengruber et al, 1995). However, we observed that in neutrophils pretreated with Y-27632 prior to addition of colchicine, F-actin was diffusely distributed in the cytosol, which is similar to results for untreated controls, suggesting a role for Rho-kinase in regulating the polarized accumulation of F-actin in colchicine-treated cells (data not shown).…”
Section: Mechanisms Of Microtubule-disruption-induced Cytoskeletal Rementioning
confidence: 72%
“…We observed previously that Rho-kinase inhibition does not affect actin reorganization in human neutrophils (Niggli, 1999). Moreover, Rho inhibition in neutrophils did not suppress chemotactic-peptide-induced actin polymerization (Ehrengruber et al, 1995). However, we observed that in neutrophils pretreated with Y-27632 prior to addition of colchicine, F-actin was diffusely distributed in the cytosol, which is similar to results for untreated controls, suggesting a role for Rho-kinase in regulating the polarized accumulation of F-actin in colchicine-treated cells (data not shown).…”
Section: Mechanisms Of Microtubule-disruption-induced Cytoskeletal Rementioning
confidence: 72%
“…The second approach is based on the use of N19Rho, a dominant-negative form of this small GTPase (9). Through the use of both approaches, it has been shown that Rho participates in a number of leukocyte functions, including the regulation of T-cell activation and pseudopodial extension (10,11), B-cell homotypic aggregation (12), chemokine-induced adhesion (13), neutrophil emigration, up-regulated adhesion (13)(14)(15), NK cell mobility and cytosolic activity (16,17), and in the maintenance of lymphocyte and monocyte shape (11,18,19).…”
mentioning
confidence: 99%
“…Studies from this laboratory and others have established that oscillations in right angle light scattering, oxidant production, and F-actin occur after stimulation of PMN in suspension, as reviewed in Coates [1996]. In most studies to date, pre-treatment of the PMN either with wortmannin, a phosphatidylinositol-3 kinase (PI3K) inhibitor, or with PMA [Wymann et al, 1987[Wymann et al, , 1989[Wymann et al, , 1990Ehrengruber et al, 1995b] was necessary to unmask an oscillatory response lasting several cycles of oscillations. Others have reported that LTB 4 or PAF induce oscillations in right angle light scattering or F-actin in the absence of any pre-treatment [Sklar et al, 1985;Omann et al, 1989Omann et al, , 1995, although no more than one oscillation cycle was clearly obtained under these conditions.…”
Section: Discussionmentioning
confidence: 98%